Tantangan Implementasi Kurikulum Merdeka di SDN Belitung Utara 1 Banjarmasin - Zahratuljannah, Adisty; Widodari, Rose; Jum’ah, Jum’ah; Syifa, Nur; Pratiwi, Diani Ayu (ARZUSIN, 2025)
This study aims to provide an in-depth description of the implementation of the Merdeka Curriculum at a public elementary school using a descriptive qualitative approach. Data were collected through interviews with the principal, who plays a central role in the planning, execution, and evaluation of the curriculum. The findings reveal that although the school demonstrates enthusiasm and commitment toward the Merdeka Curriculum, several challenges remain. These include limited teacher training, unequal digital literacy, and insufficient resources to support diverse student needs—especially those with special needs. Key components such as differentiated learning, diagnostic assessments, the integration of Pancasila Student Profile values, and parental collaboration emerged as focal points in the adaptation process. The success of the implementation heavily depends on the principal’s leadership, teacher readiness, policy support, and inter-stakeholder collaboration. This study recommends strengthening teacher capacity, optimizing the use of technology, and enhancing strategic parent engagement. In doing so, the Merdeka Curriculum can be contextually implemented in an adaptive and student-centered manner, aligning with its original purpose of promoting inclusive and meaningful learning for all students.